Strong hybrid male incompatibilities impede the spread of a selfish chromosome between populations of a fly. Issue 3 (10th May 2018) - Verspoor, Rudi L.; Smith, Jack M. L.; Mannion, Natasha L. M.; Hurst, Gregory D. D.; Price, Tom A. R.
Abstract: Meiotically driving sex chromosomes manipulate gametogenesis to increase their transmission at a cost to the rest of the genome. The intragenomic conflicts they produce have major impacts on the ecology and evolution of their host species. However, their ecological dynamics remain poorly understood. Simple population genetic models predict meiotic drivers will rapidly reach fixation in populations and spread across landscapes. In contrast, natural populations commonly show spatial variation in the frequency of drivers, with drive present in clines or mosaics across species ranges. For example, Drosophila subobscura harbors a sex ratio distorting drive chromosome (SR s ) at 15–25% frequency in North Africa, present at less than 2% frequency in adjacent southern Spain, and absent in other European populations. Here, we investigate the forces preventing the spread of the driver northward. We show that SR s has remained at a constant frequency in North Africa, and failed to spread in Spain. We find strong evidence that spread is impeded by genetic incompatibility between SR s and Spanish autosomal backgrounds. When we cross SR s from North Africa onto Spanish genetic backgrounds we observe strong incompatibilities specific to hybrids bearing SR s . The incompatibilities increase in severity in F2 male hybrids, leading to almost complete infertility. We find no evidence supporting an alternative hypothesis, that there is resistance to drive in Spanish populations. We conclude that the source of the stepped frequency variation is genetic incompatibility between the SR s chromosome and the genetic backgrounds of the adjacent population, preventing SR s spreading northward. The low frequency of SR s in South Spain is consistent with recurrent gene flow across the Strait of Gibraltar combined with selection against the SR s element through genetic incompatibility. This demonstrates that incompatibilities between drive chromosomes and naïve populations can prevent the spread of drive between populations, at a continental scale.